Pemberdayaan Masyarakat Suku Dani di Merauke melalui Pelatihan Pemasaran Digital untuk Produk Pertanian Lokal - Wakerkwa, Dian Agustina Purwanto; Indriyani, Novi (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the understanding and skills of the Dani indigenous community in Merauke Regency in utilizing social media as a marketing tool for local agricultural products. The program was implemented through training activities involving 10 female participants (mama-mama) who work as agricultural produce traders. The digital marketing training was conducted in four stages: observation, preparation, training, and evaluation. To measure the effectiveness of the program, participants were administered pre-test and post-test assessments. The evaluation results show an increase in participants’ average scores from 65 in the pre-test to 78 in the post-test, indicating a significant improvement in their understanding of digital marketing concepts. This training not only provided technical knowledge but also contributed to community economic empowerment through enhanced digital literacy. The findings demonstrate that practice-based and contextual training is effective in strengthening the capacity of local communities to respond to the challenges of the digital economy.